Populasi Mikrob Fungsional pada Rhizosfer Kelapa Sawit di Lahan Gambut Riau: Functional Microbial Population on Oil Palm Rhizosphere in Riau Peatlands - Morgan Ohiwal; Rahayu Widyastuti; Supiandi Sabiham (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2017)
Oil palm growth in peatland may influence the presence of microbial populations. Root exudate is one of the organic compounds that is released by oil palm roots in the rhizosphere area where it can be used as a nutrient for microbes to survive in peatland. The study was conducted to study functional microbial population in the rhizosphere area of oil palm plantation aged <6, 9−15, and >15 years in Riau peatlands. The highest microbial populations were found in oil palm plantation aged <6 years at peat thicknesses of <3 and >3 m, which was respectively 10.3 x 106 and 5.7 x 106 CFU g-1. The highest cellulolytic microbial population was found in oil palm plantation aged <6 years at peat thicknesses of <3 and >3m, which was respectively 17.4 x 104 and 11.4 x 104 CFU g-1. The highest Azotobacter population was found in oil palm plantation aged >15 years at peat thicknesses of <3 and >3m, which was respectively 9.4 x 105 and 12.5 x 105 CFU g-1. The highest phosphate solubilizing microbial population was found in oil palm plantation aged <6 years at peat thicknesses of <3 and >3m, which was respectively 11.4 x 104 and 13.2 x 104 CFU g-1. The highest fungal population was found in oil palm plantation aged <6 years at peat thicknesses of <3 m and >3 m, which was respectively 11.4 x 104 CFU g-1 and 17.3 x 104 CFU g-1. The highest white-rot fungal population was found in oil palm plantation aged 9−15 years at peat thicknesses of <3 m and >3 m, which was respectively 8.7 x 103 CFU g-1 and 9.4 x 103 CFU g-1. In conclusion, the highest microbial population was dominantly found in oil palm plantation aged <6 years. Keywords: Microbial populations, oil palm plantation, peat thickness, rhizosphere area